Acting, Skill, and Artistry. - CORNFORD, TOM (Shakespeare Studies (Rosemont Publishing & Printing Corporation), 2015)
The article explores both the links among acting, materiality, mimetic skill building, and rhythm in theater. Topics include the value of a more thorough understanding of the nature and operation of skill in enabling both practice and scholarship to a renewed appreciation of the artistry of the actor, the author's embarrassment in talking about skill within the context of contemporary acting, and the connection between the materiality of acting and rhythm and labor.